Odontogenic tumours: a 10 year retrospective study in South African teaching hospital - Galane, Mpatikana Leslie (My University, 2018)
Background: Odontogenic tumours (OTs) comprise a group of hamartomas, benign and malignant neoplasms arising from odontogenic epithelium entrapped within the jaws or in adjacent soft tissues. The first attempt by the World Health Organisation (WHO) to classify OTs was based on the epithelial mesenchymal interactions in these tumours. This was followed by three revisions in 1992, 2005 and 2017 following developments in immunohistochemistry and molecular biology techniques. One of the main modifications in the 2005 classification was the inclusion of odontogenic keratocyst (OKC) as a keratocystic odontogenic tumour (KCOT), due to its local aggressive behaviour and recurrence rate. Takata and Slootweg (2017) concluded that KCOT and calcifying cystic odontogenic tumour (CCOT) behave clinically as non-neoplastic lesions, and should therefore be classified as cysts. In the WHO classification (2017), KCOT and CCOT have been reclassified as OKC and calcifying odontogenic cyst (COC), respectively, until evidence that is more tangible suggests otherwise. Cemento-ossifying fibroma (COF) which occurs in the tooth-bearing areas of the jaws is engraved as a benign mesenchymal OT in the 2017 WHO classification, as it is believed to be of odontogenic origin. The aim of the study: The aim of the study was to determine the prevalence of OTs in the Department of Oral Pathology at the Wits Oral Health Centre from 2004 to 2013. Patients and Methods: The histopathology records of 392 patients diagnosed with OTs in the Department of Oral Pathology, Wits School of Oral Health Sciences, during a 10-year period were reviewed and reclassified according to the 2017 WHO classification of OTs. Clinical data including age, gender and anatomical distribution of lesions was collected and analysed. The data was captured into a Microsoft Excel spreadsheet. After cleaning, the data was imported into Stata IC/14 software for analysis. Descriptive statistics were reported for the purposes of this investigation. Continuous data (age) was analysed using parametric analysis methods and presented as mean (standard deviation) or median (minimum maximum). Frequency tables were plotted and clinico-pathological features (age, gender, race, diagnosis and site of involvement) were reported in the form of numbers and percentages. Proportions, histograms and pie charts were used to summarise these results. Results: OTs accounted for 2.87% of all oral and maxillofacial lesions (n = 13665). There were 385(98.2%) benign OTs and 7 (1.8%) malignant OTs, the latter comprised 6 carcinomas and 1 sarcoma. The 3 most common OTs in descending order of frequency were ameloblastoma (AMB) 256 (62%), cemento-ossifying fibroma (COF) 44 (11.22%) and odontogenic myxoma (OM) 29(7.40%). OTs with odontogenic epithelium in a mature fibrous stroma without odontogenic ectomesenchyme contributed 71.95% towards all the benign OTs, which attributed this group of lesions to be the most common group within all the benign OTs. AMB was the most common (92.42%) OT followed by AOT (7.58%) within OTs with odontogenic epithelium in a mature fibrous stroma without odontogenic ectomesenchyme. The mean age of patients diagnosed with OTs was 30.88 years. The mean age of patients diagnosed with conventional AMB was 33.81 years, standard deviation 15.52 years with a range of 6 to 81 years. Of all the OTs, 122 (31.12%) occurred in the first three decades of life, with a peak incidence in the second decade, 91 (23.21%). The mean age of patients with benign OTs was 27.31 years whereas the mean age for patients with malignant OTs was 47 years. The male to female ratios for benign and malignant OTs were 1: 1.1 and 1:0.8 respectively. Both benign and malignant OTs showed a predilection for the posterior region of the mandible. Conclusions: AMB was the most commonly seen odontogenic tumour. This finding is similar to those from Asian and African series. The variations observed between this study and those series are largely attributed to the 2017 WHO reclassification of OTs.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Dentistry in the branch of Oral pathology. Johannesburg, 2018